2013
DOI: 10.1159/000353400
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Daily Daptomycin in Critically Ill Patients Undergoing Continuous Renal Replacement Therapy

Abstract: Background: The optimal daptomycin dosing regimen for critically ill patients undergoing continuous renal replacement therapy (CRRT) has still to be established. Methods: Daptomycin pharmacokinetics was determined in 9 patients after administration of 6 mg/kg/day over 5 days. Results: At steady state, which was reached by day 3, the area under the curve over 24 h (AUC24h) was 667.4 ± 356.6 mg·h/l, and the maximum concentration (Cmax) was 66.9 ±25.3 mg/l. Mean CRRT clearance accounted for 48% (range 32-67%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 44 publications
5
27
0
1
Order By: Relevance
“…Although these results should be interpreted with caution due to the small sample size, the overall estimated higher clearance of daptomycin in CRRT patients is consistent with the CRRT procedure, wherein drugs and waste products are removed more efficiently on a continuous basis than with thrice‐weekly intermittent HD . Previous studies have also shown that clearance of daptomycin by CRRT accounted for approximately 40–50% of the total drug clearance , which is comparable to the amount of drug cleared by the kidneys in patients with normal renal function (34–54%) .…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Although these results should be interpreted with caution due to the small sample size, the overall estimated higher clearance of daptomycin in CRRT patients is consistent with the CRRT procedure, wherein drugs and waste products are removed more efficiently on a continuous basis than with thrice‐weekly intermittent HD . Previous studies have also shown that clearance of daptomycin by CRRT accounted for approximately 40–50% of the total drug clearance , which is comparable to the amount of drug cleared by the kidneys in patients with normal renal function (34–54%) .…”
Section: Discussionsupporting
confidence: 65%
“… (5001–5008) and Corti et al . (5009) studies; red dots in part B, observed data from the Corti et al study . CVVHD, continuous veno‐venous haemodialysis; CVVHDF, continuous veno‐venous haemodiafiltration…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations